Performance of Garden Pea Progenies for their Growth and Yield Characteristics in Mid Hills of Himachal Pradesh - Sandeep Kumar; Viveka Katoch; Akanksha Bharti (International Journal of Economic Plants)
Low genetic diversity acts as a major bottleneck in garden pea breeding and diverse parents are required to generate new genetic material. In the present investigation, fifteen hybrids were developed during 2014-15 by utilizing five lines (Line 12, Line 13, Line 14, Line 15 and Line 17) and three testers (Matar Ageta, Palam Triloki and Arkel) and, were evaluated along with their parents following randomized complete block design during 2015-16. Same material was evaluated in F2 during 2016-17. Observations were recorded for pod yield and related horticultural traits on ten randomly selected plants. On the basis of mean performance, cross line 17×Palam Triloki showed significantly best results for early traits viz., first flowering and days to 50% flowering. For pod yield, best cross was line 17×Arkel in F1. While in F2 generation, mean performance for first picking observed best for cross line 13×Palam Triloki. For pod yield, best cross was line 17×Palam Triloki. Mean pod yield plant-1 as exhibited by cross line 17×Palam Triloki was highest. Thus, cross line 17×Palam Triloki was superior in pod yield as compared to parents involved.